2018
DOI: 10.1016/j.stemcr.2018.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Telomere Rejuvenation during Chemical Induction to Pluripotent Stem Cells

Abstract: SummaryChemically induced pluripotent stem cells (CiPSCs) may provide an alternative and attractive source for stem cell-based therapy. Sufficient telomere lengths are critical for unlimited self-renewal and genomic stability of pluripotent stem cells. Dynamics and mechanisms of telomere reprogramming of CiPSCs remain elusive. We show that CiPSCs acquire telomere lengthening with increasing passages after clonal formation. Both telomerase activity and recombination-based mechanisms are involved in the telomere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 60 publications
(98 reference statements)
0
58
1
1
Order By: Relevance
“…In addition, MEFs can be good starting sources for research, but the inaccessibility of fetal tissues limits the usefulness of fetal fibroblasts in inducing CiPSCs for feasible regenerative medicine in adults. We find that crotonic acid/CS-mediated crotonylation, which activates 2C genes, including Zscan4, during induction (Fu et al, 2018), is critical for successful derivation of gPSCs from adult GCs. Single-cell analysis also revealed the critical role of activating 2C genes and Zscan4 in improving CiPSC induction (Zhao et al, 2018).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…In addition, MEFs can be good starting sources for research, but the inaccessibility of fetal tissues limits the usefulness of fetal fibroblasts in inducing CiPSCs for feasible regenerative medicine in adults. We find that crotonic acid/CS-mediated crotonylation, which activates 2C genes, including Zscan4, during induction (Fu et al, 2018), is critical for successful derivation of gPSCs from adult GCs. Single-cell analysis also revealed the critical role of activating 2C genes and Zscan4 in improving CiPSC induction (Zhao et al, 2018).…”
Section: Discussionmentioning
confidence: 87%
“…Furthermore, these gPSC lines showed limited competence to generate chimeras and failed to give rise to germline-competent offspring (Table S1). Recently, we found that crotonylation with crotonic acid (CA) or sodium (CS, crotonic acid added with 1 N NaOH to adjust the pH to approximately 7.0) at stage 2 of reprogramming activates 2-cell embryo (2C) genes, notably Zscan4, which improves induction efficiency (Fu et al, 2018). Thus, we tested and systematically compared whether CS can facilitate the generation of gPSCs from GCs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo Interventional study Mice model 2018 42 Regulation of telomere maintenance Cell culture Interventional study MEF cells 2018 44 Regulation of HIV latency Cell culture Interventional study J-Lat A1 and CD4 + T cells 2018 47 Regulation of cancer In vivo and cell culture Interventional study HCC tissues and human hepatoma-derived cell 2019 51 In general, one protein may occur simultaneously multiple PTMs. 53 Indeed, recent years gradually intensifying research on crotonylation and many publications were dedicated to only one of the many possible lysine crotonylations.…”
Section: Regulation Of Depressionmentioning
confidence: 99%
“…Ectopic expression of factors that could protect telomeres by increasing ALT-like activity, together with Zscan4, can increase the efficiency and pluripotency of iPSCs dramatically [93]. Additionally, small molecules that promote Zscan4 expression and telomeric elongation by ALT-like pathway facilitate the generation of high-quality iPSCs [94,95]. Telomeres of iPSCs are remodeled to a state resembling ESCs mainly by telomerase-dependent and possible ALT-like pathways [92,96] and continuously elongate during the acquisition of fully reprogrammed iPSCs [95].…”
Section: Alt In Pluripotent Stem Cells (Pscs)mentioning
confidence: 99%